STATUS PERLINDUNGAN BURUNG YANG DIPERDAGANGKAN DI KOTA BANDAR LAMPUNG - Kevin Alrino Damara; Sugeng P. Harianto; Dian Iswandaru; Agus Setiawan (Forestry Study Program University Of Mataram, 2022)
The rise of the hobby of raising birds in the community became an event that caused a large market demand for the availability of birds in the market. Often also found birds that are traded specifically in the city of Bandar Lampung have status as birds protected by the government, or these birds have conservation status (IUCN) and trade status (CITES) in the category that allows. This study aims to determine the protection status and conservation status of birds traded in the Bandar Lampung City area. The method used is direct observation and interviews, data analysis used is descriptive qualitative by describing according to the status of protection, trade and conservation of the types of birds obtained. The results showed there were 15 species of birds included in the list of protected wildlife according to Peraturan Menteri Lingkungan Hidup dan Kehutanan Republik Indonesia No. 106 of 2018. Birds with conservation status determined by IUCN are 50 species with status (LC), 10 species with status (NT), 1 species with status (VU), 4 status (EN) and 1 species status (CR). Birds with a trade status set by CITES, there are 1 species of birds in the Appendix 1 category and 2 species of birds included in the Appendix 2. The role of bird traders as a second hand in the trading channel, which involves pengepul, breeders and hunters. Periodic monitoring and guidance is needed as a preventif measure to reduce the risk of extinction and decline of population in the nature.